A palynological study of genus Cousinia Cass. (Family Asteraceae), sections Cynaroideae Bunge and Platyacanthae Rech. f. Issue 6 (1st November 2020) - Atazadeh, Neda; Sheidai, Masoud; Attar, Farideh; Ghahremaninejad, Farrokh; Koohdar, Fahimeh
Abstract: The genus Cousinia of the tribe Cardueae, Asteraceae, including more than 600 species, is one of the most species-rich genera in central and southwest Asia. The section Cynaroideae with 89 species is the largest section of the genus. The taxonomy of Cousinia is controversial. Using pollen morphology may be a useful tool in identifying and delimitating species. The present study therefore aims at identifying and describing species of Cousinia within the two sections Cynaroideae and Platyacanthae based on pollen features. Further, the study addresses relationships among the species based on palynological features as well as sectional and species delimitation based on pollen morphology. Pollen morphology of 28 species of Cousinia from both sections is studied for the first time using scanning electron microscopy (SEM). In this article, we present statistical analyses and multivariate statistics for palynological data. The sections Cynaroideae and Platyacanthae cannot be delimited based on pollen data. However, several pollen features useful in the taxonomic distinction between species of Cousinia were identified, including shape, size of polar axis, ratio of polar axis to equatorial diameter ( P/E ), distance between verrucae, and exine sculpturing. The relationships among the studied Cousinia species based on palynological data presented here are, in general, incongruent with results obtained from broader morphological analyses. Some possible reasons for this incongruence are proposed.